Four-Phase Interleaved Boost Converter for Maximum Power Extraction in PV System - Beauty Anggraheny Ikawanty; Bambang Irawan (Green Publisher Indonesia, 2023)
The use of renewable energy is increasing, thus affecting the rapid use of DC-DC converter technology. The use of a conventional boost converter has a weakness, namely high current ripple. This input current ripple will enter the voltage source, so that the switching noise will spread to other circuits. This problem can be overcome by using a multiphase converter topology that can suppress current ripple. But the conventional multiphase topology has large power losses, because the value of the inductor used tends to be large. Ripple currents will also reduce the efficiency of solar power plants. This study aims to design a four-phase interleaved boost converter that is applied to PV (photovoltaic) with maximum power extraction. The topology method of this circuit is to assemble a conventional boost converter in parallel up to 4 levels, so that it can suppress the input current ripple. This topology modification series also uses the interleaved scaling method in order to reduce heat distribution on each switch. The test method in this study uses a standard boost converter circuit as a comparison, and observes its characteristics and performance through simulation. The converter system is also operated as Maximum Power Point Tracking (MPPT) using the PSO and P&O algorithm controls as a comparison. Based on the simulation results, the MPPT tracking speed has the same speed, which is 2 ms, but the speed to achieve ripple stability in the standard circuit and four-phase interleaved boost converter is 4.5 ms and 6.1 ms, respectively.